Ngopi, Interaksi, dan Transaksi: Dinamika Pertukaran Sosial di Warung Secangkir Jawa, Yogyakarta - Wahyu Trisno Aji; Husain Abdul Majid; Mafaza Rohmah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This article aims to explain how encounters at Secangkir Jawa, Yogyakarta, are conducted through an analysis of George Caspar Homans' Exchange Theory. This research employs qualitative methods with a field study and an analytical approach. Data collection techniques include direct interviews with friends who frequently meet at Secangkir Jawa, and literature sources are used to strengthen the theoretical analysis. The findings demonstrate that encounters at Secangkir Jawa, Yogyakarta, are inextricably linked to the stories and interests underlying the students' presence, each with their own goals. In essence, humans are always present in interactions with their own interests and always seek profit. Analyzing this with George Caspar Homans' social exchange theory, it can be seen that encounters at Secangkir Jawa are always associated with both material and non-material interests. Looking more specifically at Homans' fundamentals, the success proposition is seen when regular encounters provide rewards, encouraging continued attendance. Meanwhile, the value proposition suggests that the greater the benefit gained, the greater the motivation to attend.